Cattle vaccination: decision making in herd health planning. Issue 2 (7th February 2013) - Paton, Neil
Abstract : Vaccines are useful for managing risk to the farm from infectious diseases. However, there are a large number of vaccines on the market and the farmer has a large number of management tasks to complete during the calendar year. This precludes the blanket usage of vaccines due to limitations of time and resources. Several factors influence the timing and type of vaccine chosen, such as the presence or absence of endemic disease on the farm and how the different vaccines work. It must also be considered that, due to the large number of vaccines administered, the probability of adverse events is quite high and client expectation should be managed with this in mind. This article addresses the rationale for choosing the most appropriate vaccination programme to meet the farmer's needs. These thoughts should be built into the herd health plan to allow the farmer to gain the most benefit from the choice of interventions.